Pengaruh Kualitas Produk, Promosi, Dan Saluran Distribusi Terhadap Keputusan Pembelian Konsumen (Studi Pada Pabrik Keripik Pisang “Metro Snack” Kota Metro) - Imron, Muhammad Ali; Suwarto, Suwarto (Universitas Muhammadiyah Metro, 2022)
THE INFLUENCE OF PRODUCT QUALITY, PROMOTION, AND DISTRIBUTION CHANNELS ON CONSUMER PURCHASE DECISIONS (STUDY ON BANANA CRIPS FACTORY “METRO SNACK” METRO CITY)” By: Muhammad Ali Imron NPM.16610189 ABSTRACT Muhammad Ali Imron Influence of Product Quality, Promotion, and Distribution Channels on Consumer Purchase Decisions (Study on Banana Chips Factory